Biosynthesis and function of simple amides in Xenorhabdus doucetiae. (13th October 2017) - Bode, Edna; He, Yue; Vo, Tien Duy; Schultz, Roland; Kaiser, Marcel; Bode, Helge B.
Summary: Xenorhabdus doucetiae, the bacterial symbiont of the entomopathogenic nematode Steinernema diaprepesi produces several different fatty acid amides. Their biosynthesis has been studied using a combination of analysis of gene deletions and promoter exchanges in X. doucetiae and heterologous expression of candidate genes in E. coli . While a decarboxylase is required for the formation of all observed phenylethylamides and tryptamides, the acyltransferase XrdE encoded in the xenorhabdin biosynthesis gene cluster is responsible for the formation of short chain acyl amides. Additionally, new, long‐chain and cytotoxic acyl amides were identified in X. doucetiae infected insects and when X. doucetiae was grown in Galleria Instant Broth (GIB). When the bioactivity of selected amides was tested, a quorum sensing modulating activity was observed for the short chain acyl amides against the two different quorum sensing systems from Chromobacterium and Janthinobacterium .